2019
DOI: 10.3389/fimmu.2019.01471
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma japonicum Soluble Egg Antigen Protects Against Type 2 Diabetes in Leprdb/db Mice by Enhancing Regulatory T Cells and Th2 Cytokines

Abstract: Type 2 diabetes is a metabolic disorder characterized by persistently elevated glucose levels. There is no effective treatment strategy for this condition, and it poses a massive economic burden globally. Schistosoma soluble egg antigen (SEA)-induced immunomodulatory mechanisms have been reported in the treatment of autoimmune disease. This study aimed to determine the ability of Schistosoma japonicum SEA to protect against type 2 diabetes in Lep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Our data showed that AES and L3ES administration ameliorates glucose intolerance and attenuates body weight gain in the treated groups. Previous findings using SEA from S. japonicum significantly reduced the level of blood sugar, however the level was still higher than those on a normal diet [26]. This was consistent with our results, as we also found that treatment with AES or L3ES of N. brasiliensis significantly reduced the blood glucose level in the diabetic group, although it was still higher than that of mice fed a normal chow diet.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showed that AES and L3ES administration ameliorates glucose intolerance and attenuates body weight gain in the treated groups. Previous findings using SEA from S. japonicum significantly reduced the level of blood sugar, however the level was still higher than those on a normal diet [26]. This was consistent with our results, as we also found that treatment with AES or L3ES of N. brasiliensis significantly reduced the blood glucose level in the diabetic group, although it was still higher than that of mice fed a normal chow diet.…”
Section: Discussionsupporting
confidence: 93%
“…This was associated with increased numbers of ILC2s, eosinophils and M2 MACs and increased levels of Th2 cytokines and the alarmin IL-33 in adipose tissue and liver [22][23][24][25]. Administration of Schistosoma japonicum SEA also protects mice against T2D via induction of Tregs and Th2 immune responses, characterised by an increase in the frequency of CD25 + Foxp3 + T cells, and elevated expression of IL-4 and IL-5 in the spleen [26].…”
Section: Introductionmentioning
confidence: 98%
“…The most commonly investigated derivatives have been soluble egg antigen (SEA) from either S. mansoni or S. japonicum, and subsequently glycan and glycoproteins found within SEA, such as the Lewis X containing Lacto-N-fucopentaose III (LNFPIII). The SEA, whether from S. mansoni or S. japonicum, consistently shows efficacy in models of IR and T2D, improving insulin sensitivity and glucose tolerance, increasing adipose M2 macrophages, increasing expression of IL-4 and -5, and increasing T regulatory cells (29,(79)(80)(81)(82). Similarly, LNFPIII has also been shown to reduce white adipose tissue inflammation and improve adipose tissue insulin sensitivity (83).…”
Section: Clinical Implications and Future Researchmentioning
confidence: 95%
“…It has also been shown that S. mansoni infection and SmSEA protect against metabolic disorders such as T2D by promoting a Th2 response, eosinophilia, and white adipose tissue (WAT) M2 (alternatively activated macrophages) polarization ( 51 ). Similarly, using a type 2 diabetes Lep r db/db mouse model, it was demonstrated that the administration of 50 µg S. japonicum SEA twice a week for 6 weeks significantly reduced insulin resistance and blood glucose and correlated with an elevation in the level of the Th2 cytokines IL-4 and IL-5 in spleen cells ( 52 ). Furthermore, the frequency of spleen regulatory T cells increased significantly in the SEA-administrated group, suggesting key roles for Th2 and Treg responses induced by SEA in reducing insulin resistance; SEA can thus provide a potential novel therapy for the treatment of T2D ( 52 ).…”
Section: Therapeutic Potential Of Live Schistosome Infection and Schimentioning
confidence: 99%